2023
DOI: 10.3390/app13031819
|View full text |Cite
|
Sign up to set email alerts
|

The Fourth Cervical Vertebra Anterior and Posterior Body Height Projections (Vba) for the Assessment of Pubertal Growth Spurt

Abstract: This paper aims to propose a statistical model to assess pubertal growth spurt using the ratio of the anterior height projection to the posterior (Vba) of the fourth cervical vertebra body (C4) on cephalograms and to calculate the residual proportion of skeletal maturation and the time for the pubertal growth spurt to end for a given Vba. A sample of 538 cephalograms from healthy-living children aged between 5 and 15 years was analyzed. A segmented regression model was used to explain the different Vba stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In science, further methods are being investigated that show promising results for certain age groups, such as age diagnosis using the fourth vertebra in a study by Gulsahi et al They investigated the correlation between age and the fourth cervical vertebra in a Turkish population group including children and young adults and could demonstrate the suitability of this method [ 22 ]. Another study by Cameriere et al also investigated the relationship between age and the fourth vertebra and developed a statistical model based on the ratio of anterior to posterior vertebral height [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In science, further methods are being investigated that show promising results for certain age groups, such as age diagnosis using the fourth vertebra in a study by Gulsahi et al They investigated the correlation between age and the fourth cervical vertebra in a Turkish population group including children and young adults and could demonstrate the suitability of this method [ 22 ]. Another study by Cameriere et al also investigated the relationship between age and the fourth vertebra and developed a statistical model based on the ratio of anterior to posterior vertebral height [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The validation process results showed that the proposed model did not produce any incorrect forecasts. Therefore, this proposed method could estimate the beginning and end of the pubertal growth spurt, together with the residual proportion of skeletal maturation for a given Vba [11].…”
mentioning
confidence: 99%